Perlindungan Ekosistem Melalui Pemberdayaan Masyarakat Sekitar Taman Nasional Gunung Merapi Daerah Istimewa Yogyakarta - Susandi, Levana Amadea; Purnomo, Eko Priyo; Ridho, Alfat (Jurnal Ilmiah Pariwisata, 2021)
This study aims to determine the efforts to protect ecosystems through empowering communities around Mount Merapi National Park (TNGM). Mount Merapi National Park is in the Special Region of Yogyakarta. TNGM is a conservation area because it is used as a means of utilizing the maintenance of living natural resources and the surrounding ecosystem. This study uses a descriptive method that provides an overview of the relationships that occur in society such as processes, activities, views and the influence of phenomena that occur. This study uses a qualitative method that provides an overview of the relationships that occur in society such as processes, activities, views and the influence of phenomena that occur in this study. The result of this research is that the protection of Mount Merapi National Park is carried out by directly involving the community in its development and empowerment. All decision-making activities that involve the community in the management of Mount Merapi National Park can be started from the planning, implementation, activities, monitoring and evaluation stages. In maintaining the ecosystem, one of them is by managing tourism such as making flower gardens, besides that the government must also be involved in monitoring community-based tourism management. Keywords: National Parks; Society; Tourism